Excessive daytime sleepiness increases the risk of motor vehicle crash in obstructive sleep apnea - Ward, Kim; Hillman, D.; James, A.; Bremner, A.; Simpson, L.; Cooper, M.; Palmer, L.; Fedson, A.; Mukherjee, S. (2013)
Study Objectives: (1) To describe the incidence rate of motor vehicle crashes (MVCs) in patients with obstructive sleep apnea (OSA); and (2) to investigate MVC risk factors in OSA patients. Methods: A retrospective case-series observational study was conducted using data from the West Australian Sleep Health Study at a tertiary hospital-based sleep clinic. Participants were patients (N = 2,673) referred for assessment of suspected sleep disordered breathing. Questionnaire data were collected including age, sex, years of driving, near-misses and MVCs, sleepiness, and consumption of alcohol and caffeinated drinks. Overnight laboratory-based polysomnography was performed using standard methodology. 1 Poisson univariate and negative binomial multivariable regression models were used to investigate associations between risk factors and MVC and nearmiss risk in patients with untreated OSA. Results: In patients with untreated OSA, the crash rate was 0.06 MVC/person-year compared with the general community crash rate of 0.02 MVC/person-year. The rate ratio comparing very sleepy men with normal men was 4.68 (95% CI 3.07, 7.14) for near-misses and 1.27 (95% CI 1.00, 1.61) for crashes, after adjusting for confounders. In women there was a signifi cant association with sleepiness score (p = 0.02) but no dose effect across quartiles. Conclusions: Untreated OSA is associated with an increased risk of near-misses in men and women and an increased risk of MVCs in very sleepy men. There is a strong association between excessive daytime sleepiness and increased report of near-misses. Our data support the observation that it is those patients with increased sleepiness regardless of OSA severity who are most at risk.